NEW VENTURES CREATION AND JUSTIFICATION IN A GLOBAL CONTEXT - Muhammad Gita Indrawan (Universitas Trisakti, 2012)
We argue that creating novel ventures consists of inductive analogical or metaphorical reasoning, which generates a platform for the creation and commercialization of novel ventures andfacilities the comprehension and justification of a vent lire. We argue that such inductive reasoning is shaped by two determinants (the applicability of prior entrepreneurial experience and the motivation to resolve uncertainly and acquire legitimacy) that interrelate to predict and explain pattern of analogical and metaphorical reasoning by which novice and experienced entrepreneurs construct meaning for themselves as well as others in the early stages of creating a venture